APPLICATION OF THE FMEA METHOD IN DETERMINING IMPROVEMENT PRIORITIES IN THE PRODUCT QUALITY SYSTEM AT COMPANY X - Antonius Cahyono; Manik Ayu Titisari; Rusdiyantoro (Sean Institute, 2023)
Company X is a manufacturing company integrated with production segments ranging from spinning, weaving, dyeing, and finishing. The company has contributed to advancing the Indonesian textile industry as an important element in the domestic production sector. However, during the production process defects often occur or the results of goods that are not in accordance with company standards often occur. The purpose of this research is to identify the causes of defects, as well as to form priority recommendations for improvement with the aim of maintaining product quality according to company standards. Data analysis applied in this study uses the Failure Modes Effect Analysis (FMEA) method. The results of this study indicate that there are 7 types of defects with the highest frequency, namely colour spots/chemical defects which are the priority for improvement in the quality system. There are 9 failure modes with the highest RPN, namely 360 in the imperfect Drug Dissolution Failure Mode. There are 5 factors that cause defects and suggestions for improvements to each problem in these factors.